Prognostic Potential of AKR1B1 in triple-negative breast cancer - Xiong Jing; Liao Xinghua; Liu Yimeng; Wang Jincheng; Fu Yufeng; Jiang Shu; Guo Hongshan (BIO Web of Conferences)
This research conducts a thorough bioinformatics examination to explore the possible function of Aldose Reductase (AKR1B1) in Triple - Negative Breast Cancer (TNBC). AKR1B1 displays heterogeneous expression patterns across various cancer types, with notably elevated levels in multiple malignancies such as bladder urothelial carcinoma, cholangiocarcinoma, and esophageal carcinoma, yet exhibiting lower expression in breast invasive carcinoma (BRCA). Utilizing the UALCAN and Human Protein Atlas (HPA) databases, a detailed analysis of AKR1B1 in BRCA reveals its distinct expression profile. Significantly, our results imply that AKR1B1 could act as a prospective biomarker in triple - negative breast cancer (TNBC). This is due to its connection with survival results and its co - expression network within this specific cancer subtype. Additionally, we delve into the complex interplay between AKR1B1 and the tumor immune microenvironment. We emphasize its notable link with CD8+ T cells and macrophages. Protein network analysis identifies key proteins interacting with AKR1B1, and experimental validation demonstrates the efficacy of curcumin in inhibiting the proliferation of TNBC cells, thereby suggesting its potential as a therapeutic agent targeting AKR1B1. This study establishes a foundational understanding of AKR1B1’s role in TNBC and paves the way for future experimental validation and therapeutic explorations.